Nonlocal State-Space Strain Gradient Approach to the Vibration of Piezoelectric Functionally Graded Nanobeam - SELVAMANI, Rajendran; LOGANATHAN, Rubine; EBRAHIMI, Farzad (Engineering Transactions, 2022)
In this work, the state-space nonlocal strain gradient theory is used for the vibration analysis of piezoelectric functionally graded material (FGM) nanobeam. Power law relations are used to describe the computing analysis of FGM constituent properties. The refined higher-order beam theory and Hamilton’s principle are used to obtain the motion of equations of the piezoelectric nanobeam. Besides, the governing equations of the piezoelectric nanobeam are extracted by the developed nonlocal state-space theory, and the analytical wave dispersion method is used to solve wave propagation problems. The real and imaginary solutions for wave frequency, loss factor and wave number are obtained and presented in graphs.